Levels of Records Keeping and Records Management among Basic Schools in Zamfara State - Almustapha, Jibril; Sani Dahiru, Abbas (International Journal of Applied Educational Research (IJAER), 2024)
This research paper was conducted purposely to determine the levels of record keeping and record management among basic schools in Zamfara State, Nigeria. To achieve this objective, two research questions were establish to guide the study. This study used survey design. A descriptive research design of survey type was employed in the study. The study population comprised all teachers in 126 government-owned basic schools in Bungudu Local Government Area of Zamfara State, Nigeria. 230 teachers were sampled through a random sampling technique using Krejie and Morgan’s Sample Size Determining Table. A structured questionnaire was developed as an instrument for data collection. Data analysis was made using descriptive statistics. The study observed that both levels of school records keeping and that of school records management was at moderate level among basic schools in Bungudu Local Government Area, Zamfara State. Based on findings, it is recommended that government should provide all the relevant/essential materials required for record keeping at the disposal of in-service teachers and other school personnel deployed in the basic schools. Also, head teachers should be exposed to modality of keeping and management the school records which should be done through workshops, effective supervisions and mentoring.